Perinatal Determinants of Child Maltreatment in Japan - Kawaguchi, Haruna; Fujiwara, Takeo; Okamoto, Yoko; Isumi, Aya; Doi, Satomi; Kanagawa, Takeshi; Kimura, Tadashi; Mitsuda, Nobuaki (Frontiers in Pediatrics, 2020)
Background: Child maltreatment induces significant health problems, both during childhood and into adulthood. To prevent child maltreatment, it is important to detect prenatal risk factors for earlier intervention. The aim of this study was to evaluate the prenatal risk factors associated with child maltreatment during pregnancy. Methods: A case-control study was conducted to compare prenatal data from the Maternal and Child Health Handbook between the case and control groups. Cases were collected from children registered in two Child Guidance Centers in Japan. The control group consisted of 3.5-year-old children in a city in Osaka Prefecture whose mothers responded to questionnaires containing information from the Maternal and Child Health Handbook. The association between prenatal factors and child maltreatment was assessed using multiple logistic regression analysis. Results: The data of 70 cases and 345 controls were collected. The following were found to be prenatal factors related to child maltreatment: teenage pregnancy (OR: 257.3, 95% CI: 17.3–3832.7), a mother aged 20–24 years (OR: 22.8, 95% CI: 4.4–117.8), a father who is older than the mother by 10 years or more (OR: 14.1, 95% CI: 2.1–94.8), a single mother (OR: 15.7, 95% CI: 2.6–93.6), maternal mental disorder (OR: 48.9, 95% CI: 9.3–258.3), the first maternal prenatal visit being later than 20 weeks (OR: 132, 95% CI: 12.7–1384.7), little prenatal care (less than 10 visits) (OR: 21.4, 95% CI: 2.9–157.1), a low-birth-weight baby (OR: 5.1, 95% CI: 1.1–24.1), and congenital disease (OR: 7.9, 95% CI: 1.1–56.4). Conclusions: This study revealed that young mothers, fathers much older than mothers, single mothers, and maternal mental disorder, mothers with late first visit or little perinatal care, and low-birth-weight babies and babies with congenital disease were associated with child maltreatment. These findings can be used to detect high-risk families for child maltreatment during or after pregnancy.